PERAN ILMUWAN DALAM PEMBUATAN KEBIJAKAN FISKAL HIJAU: STUDI KASUS PROVINSI JAMBI - Fitri Nurfatriani,S.Hut,M.Si; Dudung Darusman; Dodik Ridho Nurrochmat; Ahmad Erani Yustika; Fentie Salaka (Jurnal Analisis Kebijakan Kehutanan, 2018)
Forest functions as a provider of environmental services and non-timber forest products (NTFP) should be considered in the fiscal transfer mechanism of central and local governments. Thus, it is necessary to shift the direction of fiscal policy in the forestry sector from timber revenue to green fiscal policy. The preparation of the green fiscal policy framework requires a series of stages analysis: policy instruments, stakeholder and the role of scientists in the formulation of green fiscal policy. The objective of this study is to analyze the role and influence of scientists in green fiscal policy making. Scientists are expected to be a bridge so that the concept of green fiscal funding policy can be formulated and implemented based on scientific theories. This research was conducted in Jambi Province. Data collection and information was done through interview, observation and literature study. Data were analyzed using scientist classification matrix that influenced the policy making process based on the level of independence and its influence. The results showed that the role and position of scientists in green fiscal policy making is divided into the honest broker of policy alternative and advocate issues,. The influence of scientists is limited to the preparation of academic texts.